2020
DOI: 10.1177/1534735420941605
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Center-Based Delivery of Tai Chi and Qi Gong Group Classes on Self-Reported Symptoms in Cancer Patients and Caregivers

Abstract: Background: There is increasing interest in complementary approaches such as Tai Chi (TC) and Qi Gong (QG) in oncology settings. We explored the effects of TC/QG delivered in group classes at a comprehensive cancer center. Methods: Patients and caregivers who participated in TC or QG completed assessments before and after an in-person group class. Assessments included questions about expectancy/satisfaction and common cancer symptoms (Edmonton Symptom Assessment Scale [ESAS]). ESAS distress subscales analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Luberto et al [73] found that the practice of tai chi by patients with heart failure improved their depression symptoms and quality of life indexes. Lopez et al [74] found that group tai chi and qigong classes taken by cancer patients and caregivers experienced significant improvement in global distress. Zhang et al [75] performed a meta-analysis and evaluation of tai chi chuan on anxiety and depression on 14 experimental studies.…”
Section: Resultsmentioning
confidence: 99%
“…Luberto et al [73] found that the practice of tai chi by patients with heart failure improved their depression symptoms and quality of life indexes. Lopez et al [74] found that group tai chi and qigong classes taken by cancer patients and caregivers experienced significant improvement in global distress. Zhang et al [75] performed a meta-analysis and evaluation of tai chi chuan on anxiety and depression on 14 experimental studies.…”
Section: Resultsmentioning
confidence: 99%
“…Qi Gong may serve as a promising opportunity to improve psychological health domains such as the quality of life, depressive symptoms, fear of falling, and sleep quality in older adults ( 119 ), potentially having a beneficial effect on symptoms of anxiety ( 120 ), potentially effective to improve gait speed, balance, activities of daily living, and mobility to be a promising complementary therapy in Parkinson's Disease ( 121 , 122 ), significant improvement in fatigue, and global distress in oncology patients ( 123 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there is an increasing interest in mindbody interventions (MBIs), such as Tai Chi, in oncology settings, which may provide a new and effective treatment for CRF. 10 The National Center for Complementary and Integrative Health defined MBIs as 'techniques designed to enhance the mind's capacity to affect bodily function and symptoms'. 11 MBIs have been shown to be effective in decreasing the expression of inflammation-related genes and in reducing common cancer-related side effects, especially in alleviating fatigue symptoms.…”
Section: Open Accessmentioning
confidence: 99%